Evaluating the genotoxic and cytotoxic effects of synthetic nucleosides in vitro - Haskins, Jeremy S., author; Kato, Takamitsu A., advisor; Leary, Del, committee member; Bouma, Gerrit, committee member (Colorado State University. Libraries, 2019)
The convoluted interplay between various cellular organelles has been a prominent area of study since humans have had the ability to research and explore the microscopic cellular world. Particularly, significant attention has been exercised in the effect that various compounds, pharmaceuticals, drugs, and therapies have on cellular division; particularly cancer cell division. Although documentation is scant, monitoring cell division has been of great interest for years. The utilization and administration of tritiated thymidine, to visualize cellular replication, was unarguably the first strategy to monitor cellular division. However, this method was deemed toxic and cumbersome. 5-bromo-2'-deoxyuridine (BrdU) soon took high notoriety. BrdU, a halogenated pyrimidine, and its structurally related analogs are known to mimic the deoxynucleoside, thymidine, during S-phase of cellular replication. BrdU is incorporated in place of thymidine during S-phase, and its rate of incorporation can be monitored via immunohistochemical antibody detection. However, current literature has demonstrated that BrdU presents a number of complications regarding long-term labeling, cell cycle progression, cellular mutagenicity and cytotoxicity, and unwanted photosensitivity. BrdU's shortcomings were bypassed by the advent of 5-ethynyl-2'-deoxyuridine (EdU) (25). EdU, an additional synthetic analog of thymidine, having a terminal 5'-ethynyl- substituent, instead of thymidine's or BrdU's terminal 5'-methyl- or 5'-bromo- substituent, respectively. EdU has gained popularity as the preferred method in detecting cellular division due to its inherent ability to readily incorporate into newly synthesized DNA. In order to detect and incorporate BrdU into DNA, the process requires the expenditure of an antibody. Binding of the BrdU-antibody tandem to DNA necessitates denaturation of DNA via volatile acid or heat treatment, which presents complications as unqualified and unfaithful base-paring and reannealing. Conversely, EdU incorporation and detection is a fast, simple, and effective method in labeling actively dividing cells. By way of "click" chemistry, EdU is readily introduced and synthesized into new DNA. The latter is accomplished, in part by a small-sized fluorescent azide, qualifying easy access to DNA without considerable steric hindrance. It is expected that successful incorporation of EdU, via "click" chemistry will result in high resolution microscopy analysis. However, current research suggests that implementation of EdU may result in unwanted biological effects. Using an in vitro system, the experimental basis described herein sought to determine the effects that BrdU or EdU had on cell cytotoxicity and genotoxicity when incorporated in DNA. Whilst a vast majority of research experiments use concentrations of said nucleosides' in the range of 10-50 µM, these conditions may induce strong genotoxic and cytotoxic effects inherently higher than the expected background frequency. By treating various DNA repair deficient cells with BrdU or EdU, at concentrations ranging from 1-100 µM, there was a significant increase in the induction of sister chromatid exchanges. Also, with identical concentrations as the latter, the doubling time of particular DNA repair deficient cell lines increased dramatically. To examine the effects of BrdU and EdU on DNA repair, a poly (ADP ribose) polymerase (PARP) ELISA assay was carried out. The PARP assay concluded that BrdU possessed the highest degree of PARP inhibition, with thymidine second, and EdU with the least PARP inhibition. One suggested mechanism by which BrdU is thought to implicate or hinder DNA repair is through its incorporation and modification of DNA repair thus, slower repair kinetics. Hypoxanthine-guanine phosphoribosyltransferase (HPRT) mutation analysis suggests that manufacturers recommended EdU concentration (10µM), result in a significantly higher HPRT mutation frequency, compared to control. In addition to BrdU's SCE-induction capability and HPRT-induction incidence, clinical and radiotherapeutic properties have been examined. CHO cells exposed to 2 and 8 µM BrdU and 4 or 15 Gy X-rays, increase DNA repair duration, increased chromosomal fragmentation, and induce radiosensitization. However, little or no evidence is available in regard to EdU's propensity to affect cell viability. To assess the induction of cellular radiosensitivity and chromosomal aberrations, we investigated CHO and A549 (human lung cancer) cells replicative ability in the presence of three external radiation. An in vitro clonogenic and chromosomal aberration assay, in the presence of UVC-, photon (fluorescent)-, and γ-irradiation and BrdU or EdU, was implemented. Our results support BrdU's ability to decrease cell viability. Although each synthetic analogue presented their own biological contribution, their mechanism is still not fully understood. This study aims to discern any cytotoxic and/or genotoxic effects that EdU or BrdU pose on cell cycle progression, clonogenicity and viability, mutation-induction, chromosomal aberrations, and induction of radiosensitization.